Comparison of pancreatic histology specimens obtained by EUS 19G versus 22G core biopsy needles: A prospective multicentre study among experienced pathologists. Issue 6 (October 2017) - Petrone, Maria Chiara; Poley, Jan-Werner; Bonzini, Matteo; Abdulkader, Ihab; Biermann, Katharina; Monges, Genevieve; Rindi, Guido; Doglioni, Claudio; Bruno, Marco J; Giovannini, Marc; Iglesias-Garcia, Julio; Larghi, Alberto; et al.
Background and aim: Scanty data about inter-observer agreement (IOA) among pathologists in the evaluation of pancreatic samples acquired with EUS histology needle are available. The aim of this study was to determine IOA on adequacy of pancreatic histology specimens obtained with a 22G needle by a panel of experienced pathologist, in comparison with the 19G needle. Methods: This multicentre prospective study involved 73 pancreatic specimens prepared using histology needles of different calibres. Five pathologists independently reviewed all the samples, assessing the presence of a core, specimen adequacy and the possibility to perform additional analyses. IOA determined by Fleiss' Kappa statistic was used as the primary outcome measure. Secondary outcome was to compare 22G versus 19G needle results. Results: A core was present in 57% of pancreatic specimens obtained by 22G needle. The specimens were considered adequate in 72% of cases, with poor agreement among pathologists ( p  = 0.02, Fleiss' κ = 0.26). The possibility to perform further analyses was rated as 'positive' in 66% of cases without significant difference among observers ( p  = 0.80). When comparing the results, the presence of a core and the adequacy of tissue slides were significantly better for the 19G needle (57% vs. 84% p  = 0.002; 72% vs. 83% p  = 0.004, respectively). Reproducibility in the assessment of pancreatic sample adequacy was significantly better with the 19G needle (κ = 0.26 for 22G samples vs. κ = 0.81 for 19G samples). Conclusions: Our results suggest that histology sampling of pancreatic masses should be performed with a 19G histology needle, since is able to provide a core in the majority of cases, with 83% of adequate specimens and excellent results in term of reproducibility among pathologists.